A Cooperative Industry - Government Woodland Caribou Research Program in Northeastern Alberta - Rippin, Blair; Edey, Colin; Hebert, Daryl; Kneteman, Jeff (Rangifer, 1996)
Rapid development of large scale logging and increasingly intensive petroleum exploration and development in northeastern Alberta prompted the establishment of a cooperative research program to investigate various aspects of woodland caribou (Rangifer tarandus caribou) biology. The ultimate goal of the program is to develop an effective plan that will ensure the long term survival of caribou while allowing for renewable and non-renewable resource development. There are three parts to the program. Part I began early in 1991 and makes use of conventional radio telemetry as a means of recording various parameters of general caribou biology. The study area encompasses approximately 4000 km2 of low relief, boreal mixedwood forest. Preliminary results from 2500 radio locations (involving 50 individuals) indicate that woodland caribou inhabiting the study area are non-migratory and are strongly associated with some of the more scarce peatland forest types present in the area. Investigations to document the basic biology and ecology will continue for another two years. Part II began in early 1993 as a part of a two-year investigation into the disturbance effects of petroleum exploration and development on caribou movements and behaviour. One objective of this study is to develop a predictive model useful in determining the cumulative effects of varying intensities of disturbance on caribou. Part III began in early 1994 with a proposed three-year investigation to determine the mechanism of spatial and temporal separation of caribou and moose in the study area. These relationships may indicate the means by which caribou minimize the impact of wolf predation on their populations in northeastern Alberta. Results will be applied to industrial land use and specifically to large scale forest harvesting planned for the area. The research program is supported through cooperative funding contributed by 24 petroleum companies, 1 forest company, 2 peat companies and the Alberta Departments of Environmental Protection and Energy. The research aspect of the program has been developed and implemented by staff of the University of Alberta, Alberta-Pacific Forest Industries, the Alberta Fish and Wildlife and Forest Services and the Alberta Environmental Centre. The program also incorporates a public information and liaison function. Newsletters, information videos, brochures and public consultation are the means used to accomplish this task.